The Influence of The Time Token Model on The Social Science Learning Outcomes of Class IV Students of Private Primary School 125138 Pematang Siantar - Jenew Year Manurung; Osco Parmonangan Sijabat; Sukardo Sitohang (International Journal of Integrated Science and Technology, 2023)
This research aims to find out whether the use of the Time Token Model has an influence on the learning outcomes of Class IV Students at SD Negeri 125138 Pematang Siantar on theme 3 Caring for Living Creatures with sub-theme 1 Animals and Plants in My Home Environment in lesson 1 at SD Negeri 125138 Pematang Siantar. There are 2 hypotheses in this research, namely (1) there is an influence of the Time Token Model user on the Social Sciences Learning Outcomes of Class IV Students at SD Negeri 125138 Pematang Siantar (H a ) and there is no influence of the Time Token Model on the Social Sciences Learning Results of Class IV Students of SD Negeri 125138 Pematang Siantar (H 0 ). Pre-Experimental Design research type that uses a One Group Pretest-Posttest Research Design. The population of this study was all fourth grade students at SD Negeri 125238 Pematang Siantar, totaling 30 students. Data collection was carried out using test and observation techniques. This research data was analyzed using descriptive and inferential statistical analysis. Based on the results of data analysis, it is known that the t count is 15.112 with a significance level of 0.05. So it can be concluded that there is an influence of the Time Token Model on the Social Sciences Learning Outcomes of Class IV Students at State Elementary School 125138 Pematang Siantar sub theme 1 animals and plants in my home environment means that H a is accepted and H 0 is rejected.